2022
DOI: 10.1093/ajcn/nqab406
|View full text |Cite
|
Sign up to set email alerts
|

Maternal iron kinetics and maternal–fetal iron transfer in normal-weight and overweight pregnancy

Abstract: Background Inflammation during pregnancy may aggravate iron deficiency by increasing serum hepcidin and reducing iron absorption. This could restrict iron transfer to the fetus, increasing risk for infant iron deficiency and its adverse effects. Objectives To assess whether iron bioavailability and/or iron transfer to the fetus is impaired in overweight/obese (OW) women with adiposity-related inflammation, compared to normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Naïve T cell diseases due to decreased uptake 335,336 and does not improve the iron status in obese patients. 46,337 In the presence of low-grade inflammation, clinical trials have shown that the addition of vitamin A, 338 vitamin C, 140,310 antioxidants improve dietary iron uptake. Low-hemoglobin levels in pregnant women were also negatively correlated with the breast milk iron content.…”
Section: Th1 Th2mentioning
confidence: 99%
See 1 more Smart Citation
“…Naïve T cell diseases due to decreased uptake 335,336 and does not improve the iron status in obese patients. 46,337 In the presence of low-grade inflammation, clinical trials have shown that the addition of vitamin A, 338 vitamin C, 140,310 antioxidants improve dietary iron uptake. Low-hemoglobin levels in pregnant women were also negatively correlated with the breast milk iron content.…”
Section: Th1 Th2mentioning
confidence: 99%
“…Though calcium can impede iron absorption, this only seemed to be true to a modest degree of about 20%, when excessive high amount of calcium was consumed 330–334 . Iron absorption is impeded upon immune activation due to hepcidin, and thus oral iron may even enhance disease activity in inflammatory bowel diseases due to decreased uptake 335,336 and does not improve the iron status in obese patients 46,337 …”
Section: Ironmentioning
confidence: 99%
“…Maternal pregestational overweight/obesity has been hypothesized to increase the risk of childhood anemia [ [53] , [54] , [55] ]. A recent prospective study that followed up pregnant women and their infants to 6 mo of age from 3 different countries (Switzerland, Mexico, and Thailand) found that, when compared to pregnant women with normal weight, those with overweight/obesity showed impaired iron absorption in late pregnancy, transferred less iron to their fetuses, and their infants had lower body iron stores [ 56 ]. Likewise, maternal obesity increases the risk of fetal macrosomia, which in turn, may lead to inflammation, a rise in hepcidin levels, and over time, result in anemia of inflammation [ 55 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Iron status depends not only on total iron intake but also on the absorption and availability of iron in the body [ 23 , 37 ]. Haem iron is absorbed more easily from the main sources, which are meat and fish [ 38 ].…”
Section: Discussionmentioning
confidence: 99%